PERANCANGAN TANGKI BIOGAS PORTABEL SEBAGAI SARANA PRODUKSI ENERGI ALTERNATIF DI PEDESAAN - M. C. Tri Atmodjo; Dadang Rosadi; Hardoyo Hardoyo (Widyariset, 2014)
The increasing price of fossil-based energy and the higher amount of its consumption amidst its limited source would be the main reasons to develop some alternative energy from renewable sources. One of such alternative energy sources is the one from biomass waste, which is easy to find in rural areas as well as in animal husbandry. This biogas portable tank is designed for 160 liters of volume and 75% of this volume is filled with slurry which composes 1 part of cow manure and 1 part of fresh water. The Hydrolysis Retention Time of this slurry is about 20 days and everyday 14.5 liters of old slurry is replaced with the new one and will produce biogas by about 0.56 until 0.68 cubic meters per day, equal to 0.26 kg of LPG. By the assumption that the price of LPG is Rp6,000 per kg and 30 days of operation in a month, the biogas portable tank would get revenue which can cover cost production of the tank in less than 2 years of operation. With its simple design, small scale and lower cost production, and operability, the biogas portable tank is suitable for the production process of biogas and for fulfilling energy needs in rural areas.